PENGEMBANGAN E-MODUL PEMAHAMAN KARIER UNTUK PESERTA DIDIK SMA - Non Syafriafdi; Khairiyah Khadijah; Suherman Syahputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to develop an E-Module on Career Understanding to improve the foundation related to self-understanding and the career world of high school students. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The resulting product was validated by subject matter experts, media experts, and language experts, and tested on a small group of 10 students from Pekanbaru 1 Public High School. The validation results showed that the Career Understanding E-Module was declared highly valid by subject matter experts (92.05%), media experts (100%), and language experts (98.33%). The small group trial also produced positive responses with a practicality percentage of 95.60%, indicating that this module is effective and easy to use by students. This E-Module is designed with interactive features such as gamification, videos, and animations to facilitate career understanding, covering self-understanding, work world exploration, and career planning materials. This research contributes to the field of guidance and counseling by providing innovative digital media to help high school students plan their careers. Recommendations for further research include expanding the scope of the material and conducting effectiveness tests on a larger scale.